Folate status in type 2 diabetic patients with and without retinopathy - Malaguarnera G (Dove Medical Press, 2015)
Giulia Malaguarnera,1 Caterina Gagliano,2,3 Salvatore Salomone,1 Maria Giordano,4 Claudio Bucolo,1 Antonino Pappalardo,5 Filippo Drago,1 Filippo Caraci,6,7 Teresio Avitabile,2 Massimo Motta51Department of Biomedical and Biotechnological Sciences, University of Catania, Catania, Italy; 2Department of Ophthalmology, University of Catania, Catania, Italy; 3Neurovisual Science Technology (NEST), Catania, Catania, Italy; 4Gerontology and Bone Metabolic Disease Section, Department of Medical Sciences, University of Turin, Turin; 5Department of Medical and Paediatric Sciences, University of Catania, Italy; 6Department of Drug Sciences, University of Catania, Catania, Italy; 7IRCCS Association Oasi Maria S.S.-Institute for Research on Mental Retardation and Brain Aging, Troina, Enna, ItalyBackground: Folate deficiency is associated with cardiovascular disease, megaloblastic anemia, and with hyperhomocysteinemia. This study has been undertaken to investigate the role of folate status during the progression of the diabetic retinopathy.Methods: We measured the plasma levels of homocysteine, folic acid, and red cell folate in 70 diabetic type 2 patients with nonproliferative diabetic retinopathy (NPDR), 65 with proliferative diabetic retinopathy (PDR), 96 without diabetic retinopathy, and 80 healthy subjects used as a control group.Results: We found higher plasma levels of homocysteine in the NPDR group compared to the control group (P<0.001) and in the PDR group compared to control group (P<0.001) and NPDR group (P<0.01). The severity of diabetic retinopathy was associated with lower folic acid and red cell folate levels, and a significant difference was observed between PDR and NPDR groups (P<0.05).Conclusion: The folate status could play a role in the development and progression of diabetic retinopathy. Keywords: homocysteine, proliferative diabetic retinopathy, nonproliferative diabetic retinopathy, diabetes mellitus